On Wijsman Asymptotically Deferred Statistical Equivalence of Order a for Set Sequences - Et, Mikail; Altinok, Hifsi; Colak, Rifat (Amer Inst Physics, 2018)
In this study we introduce the concepts of Wijsman asymptotically deferred statistical equivalence of order a and Wijsman strong deferred Cesaro asymptotically equivalence of order a for set sequences.
6th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 15-17, 2017 -- Budapest, HUNGARY
Keywords: Convergence; Alpha